Metodología en la enseñanza de los fundamentos básicos del baloncesto en la básica superior de la Escuela Ciudad de Machala - Román Cadena, Ariel Alberto; San Martin Quizhpe, Ariel Alexander (Machala : Universidad Técnica de Machala, 2022)
The present research work is an integrative project, and focused on the inadequate methodology for the development of the basic fundamentals of basketball in the upper basic whose objective was oriented in Analyzing the Teaching Methodologies of the basic fundamentals of basketball that apply teachers in physical education classes in the upper basic school of the city of Machala and as a specific objective: Determine the teaching methodologies for the development of the basic fundamentals of basketball through literary review, Identify the mastery of the teacher of the subject of physical education in the management of teaching methodologies and determine the orientation that teachers of the subject of physical education need regarding teaching methodologies. The data collection was based on the mixed approach, with a descriptive methodology, managing to diagnose the reality in the Ciudad de Machala school in relation to the Teaching Methodologies and the Basic Fundamentals of Basketball The methods with the greatest incidence in this investigation is the analytical-synthetic and others that were integrated as auxiliaries, such as the bibliographical one, which contributed significantly at the time of collecting the information based on the specific objectives to contribute to the general objective, literature, with field research and finally to support the integrating proposal, as a contribution in favor of the educational institution that facilitated access to carry out the research. In relation to the sample, all physical education teachers were considered, since the number is three. The selected instruments were the survey and the interview that for its construction related the objects of study, from which four dimensions were derived and consequently the indicators served as a guide for the elaboration of the instruments with a Likert scale, which facilitated the reception of opinions and attitudes of the people involved in this work and at the same time score the range of values from fixed answers. The analysis of the results in the survey shows that teachers do not master methodologies for teaching the basic fundamentals of basketball. Due to the foregoing and responding to the third specific objective, the integrating proposal was defined, which was oriented to elaborate the teaching methodologies of the basic fundamentals of basketball that the teachers will apply in the physical education classes in the upper basic of the Ciudad de Buenos Aires school. Machala as a contribution to improve the dynamics of the methodological process. The proposal consisted of three phases, elaboration of the proposal, socialization and evaluation of the same, In addition, the logistical resources and the evaluation of the feasibility with the dimensions, technical, economic, social and environmental were included, demonstrating the capacity to achieve the objectives of the proposal, determining the viability and material capacities that the proposal has. The investigative work concluded by establishing the conclusions, recommendations, limitations and prospective. he same ones that were written to cover aspects related to the revision
El presente trabajo de investigación se trata de un proyecto integrador, y se centró en la inadecuada metodología para el desarrollo de los fundamentos básicos del baloncesto en la básica superior cuyo objetivo se orientó en Analizar las Metodologías de enseñanza de los fundamentos básicos del baloncesto que aplican los docentes en las clases de educación física en la básica superior de la escuela ciudad de Machala y como objetivo específico, Determinar las metodologías de la enseñanza para el desarrollo de los fundamentos básicos del baloncesto mediante revisión literaria, Identificar el dominio del docente de la asignatura de educación física en el manejo de las metodologías de enseñanza y Determinar la orientación que necesitan los docentes de la asignatura de educación física respecto a las metodologías de enseñanza. La recopilación de datos se fundamentó desde el enfoque mixto, con una metodología de carácter descriptivo, logrando diagnosticar la realidad en la escuela Ciudad de Machala en relación con las Metodologías de enseñanza y los Fundamentos básicos del baloncesto, los métodos de mayor incidencia en esta indagación es el analítico-sintético mismo que aportaron significativamente al momento de recabar la información con base en los objetivos específicos para contribuir al objetivo general, mismos que estuvieron redactados para abarcar aspectos relacionados con la revisión literaria, con la investigación de campo y finalmente para sostener la propuesta integradora, como aporte a favor de la institución educativa que facilitó el acceso para concretar la investigación. En relación con la muestra se consideró a todos los docentes de educación física, puesto que el número es de tres. Los instrumentos seleccionados fueron la encuesta y la entrevista que para su construcción se relacionó los objetos de estudio, de donde se derivaron cuatro dimensiones y en consecuencia los indicadores sirvieron de guía para la elaboración de los instrumentos con una escala de Likert, que facilitó la recepción de opiniones y actitudes de las personas involucradas en este trabajo y al mismo tiempo puntuar a partir de respuestas fijas el rango de valores. El análisis de resultados en la encuesta se demuestra que los docentes no dominan metodologías para la enseñanza de los fundamentos básicos del baloncesto. Por lo que antecede y respondiendo al tercer objetivo específico, se definió la propuesta integradora que se orientó a elaborar las metodologías de enseñanza de los fundamentos básicos del baloncesto que aplicarán los docentes en las clases de educación física en la básica superior de la escuela Ciudad de Machala como aporte para el mejoramiento de la dinámica del proceso metodológico. La propuesta estuvo compuesta de tres fases, elaboración de la propuesta, socialización y evaluación de la misma, además, se incluyó los recursos logísticos y la valoración de la factibilidad con las dimensiones, técnica, económica, social y ambiental, demostrando la capacidad para lograr los objetivos de la propuesta, determinando la viabilidad y capacidades materiales con los que cuenta la propuesta. El trabajo investigativo concluyó estableciendo las conclusiones, recomendaciones, limitaciones y prospectiva.
Keywords: METODOLOGIA; ENSEÑANZA; FUNDAMENTO BASICO; BALONCESTO